Development of Scientific Literacy-Based Student Worksheets (LKPD) for the Classification of Living Organisms Learning Materials - Ali, Sri Herawati; Solikha, Maratus; Paujiah, Epa; Mas’ud, Asrianty; Cahyanto, Tri (Journal of Educational Sciences, 2025)
Indonesian students’ scientific literacy remains relatively low, as indicated by PISA results, which placed Indonesia among the bottom 10 countries, and AKMI data shows that 51% of madrasah students are at the "basic" level. This study aims to develop scientific literacy-based Student Worksheets (LKPD) on classifying living organisms for learning. The research method employed is Research and Development (R&D) using the 3D model, which includes the Define, Design, and Develop stages. The research subjects included material and media expert validators, a class X biology teacher, and 25 class X students at MAN 1 Bandung. The instruments used were validation sheets, readability questionnaires, and student response questionnaires. Data analysis was conducted using qualitative and quantitative approaches with the help of a Likert scale. The results showed that the developed LKPD is feasible for use, with material expert validation at 85.556% (highly valid), media expert validation at 72.25% (valid), teacher readability at 80.80% (easy to understand), student readability at 85.35% (easy to understand), and student responses at 86% (highly positive). Therefore, the scientific literacy-based LKPD on the classification of living organisms is suitable for use and can serve as effective teaching material to support the learning process.